2009
DOI: 10.1042/bst0371126
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function studies for the panacea, valproic acid

Abstract: The anticonvulsant properties of VPA (valproic acid), a branched short-chain fatty acid, were serendipitously discovered in 1963. Since then, therapeutic roles of VPA have increased to include bipolar disorder and migraine prophylaxis, and have more recently been proposed in cancer, Alzheimer's disease and HIV treatment. These numerous therapeutic roles elevate VPA to near 'panacea' level. Surprisingly, the mechanisms of action of VPA in the treatment of many of these disorders remain unclear, although it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 68 publications
0
96
0
Order By: Relevance
“…VPA is primarily used for the treatment of epilepsy and bipolar disorder treatment, although it has numerous molecular mechanisms and effects (Terbach and Williams, 2009), including the inhibition of cPLA2 (Bazinet et al, 2006) and the regulation of lipid homeostasis (Elphick et al, 2012). Here we show that synapse damage caused by Aβ, is reduced by VPA and a structural derivative (propylisopropylacetic acid (PIA)).…”
Section: Introductionmentioning
confidence: 78%
“…VPA is primarily used for the treatment of epilepsy and bipolar disorder treatment, although it has numerous molecular mechanisms and effects (Terbach and Williams, 2009), including the inhibition of cPLA2 (Bazinet et al, 2006) and the regulation of lipid homeostasis (Elphick et al, 2012). Here we show that synapse damage caused by Aβ, is reduced by VPA and a structural derivative (propylisopropylacetic acid (PIA)).…”
Section: Introductionmentioning
confidence: 78%
“…The drug is used as antiepileptic and to dampen bipolar disease. The clinical mode of action is supposed to involve inhibition of gamma aminobutyric acid degradation, but it may also involve modulation of ion channels, wnt signaling and altered phosphoi nositol turnover (Rosenberg, 2007;Terbach and Williams, 2009;Williams et al, 2002). Moreover, VPA is a well known develop mental neurotoxicant that induces severe malformations when taken during pregnancy (Ornoy, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the various opinions on the action of VPA on membrane ion channels, intracellular messenger systems, amino acid release, and metabolism of monoamines, the vast majority of researchers agree that the main neuropharmacological effect of this drug is the enhancement of GABAergic transmission and a rise in GABA levels in the central nervous system (37)(38)(39)(40)(41)(42)(43). In this study, a reduced GABA level in the hypothalamus was observed in the PAAC group, but VPA significantly boosted the GABA level in the region as well as sympathetic inhibition.…”
Section: Discussionmentioning
confidence: 99%